PERANAN PEMERINTAH DESA ANABANNAE DALAM PENANGGULANGAN KEMISKINAN - Fyngky, Fryza; Jabbar, Abdul; Hakim, Akhyaruddin (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research aims to determine the extent of the village government's role in poverty alleviation efforts in terms of several existing programs in Anabannae Village, Pitu Riawa District, based on indicators, as well as what obstacles hinder this role. The research method used is a qualitative method accompanied by an individual phenomenological approach, where the data source is obtained through an interview and documentation process. Data analysis was carried out based on several stages, namely data reduction, data classification, data description, and drawing conclusions. The results of this research show that (4) the role in poverty alleviation has not been fulfilled optimally because there are several obstacles, namely community participation, low skills and facilities.